Jaringan Sosial dan Konvergensi Media: Penonton Interaktif Sinetron 7 Manusia Harimau - Margareta Wulandari; Novi Kurnia (Jurnal ILMU KOMUNIKASI, 2017)
In the convergence era, television audience has become interactive audience. Study about television audience become important, especially in favorite program, such as sinetron (Indonesian soap opera). Netnography method is used to examine the social network dynamics of 7 Manusia Harimau audience. After conducting online participatory observation in two fandom groups and in-depth interviews with seven informants, the results show that media convergence has broaden the way audience consume sinetron and enhanced the audiences’ interactivity. Online media support the audience to develop individual and communal network, collective identity and intelligence, collective actions and participatory culture.